Active reflection coefficients characterization system for multiple input multiple output antennas. Issue 5 (10th March 2021) - Jordão, Marina; Belo, Daniel; Caldeirinha, Rafael F. S.; Oliveira, Arnaldo S. R.; Carvalho, Nuno B.
Abstract: The main objective of this study is to present a characterization system that can be used to measure the active reflection coefficient of each port of the multiple input multiple output (MIMO) antennas, when the main beam is steered to an intended direction. Since MIMO systems are composed of antennas with several elements and each antenna element is connected to a power amplifier, an active component, the beamforming will contribute to the mismatch of each branch. To this extent, a calibrated measurement system has been implemented using off‐the‐shelf software defined radio and designed to effectively extract such coefficients, when all the ports are simultaneously excited. Results for linear and planar MIMO antenna arrays have been experimentally obtained for several beam directions and the impact of beamforming on each element of the antenna is presented and compared to simulated results. Additionally, their behaviour was also assessed when some of the radiation elements are deliberately disconnected, mimicking those not working properly.